Pengembangan LKS Berbasis Pendekatan Pemodelan Matematika Untuk Melatih Kemampuan Koneksi Matematis Siswa SMP Kelas VIII - Astuti, Puji; Hartono, Yusuf; Bunayati, Hanifah; Indaryanti (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2017)
National Council of Teacher of Mathematics (NCTM) stated five basic mathematics skills: problem solving, proof and reasoning, communication, connections, and representation. In an effort to explore and develop students' mathematical communication ability, mathematical modelling approach was used in mathematics learning of VIII-grade SMP Negeri 13 (state Junior High School) Palembang. This research is a development research aims to develop student worksheet based on mathematical modelling approach. Document analysis shows that the worksheet is valid and practical. Test data shows potential effect with some categories of students’ mathematical connections ability: 66.67% “good”, 21.21% categorized as